Data Forecasting to Assist Software Verification & Validation Strategy Preparation - Sadikin, Mujiono (Proceeding Information Technology, 2013)
Abstract â Software verification and validation is a critical phase in software development projects. But unfortunately in many software development projects, software verification and validation rarely gets sufficient attention. Lack of attention is partly due to the assumption that the software verification & validation is not a priority and there for only limited resources can be allocated. This paper presents the result of study in using forecasting analysis model to assist software test strategy preparation. This study applies forecasting analysis to accumulation of individual transaction data that have been got before the system is tested. Those forecasting results are used as comparison tool to compare with the transaction data generated by system which is being tested. This study use subsidized fuel consumption monitoring system as a case study to apply the forecasting model. Test results on the case study, with some limitations, show that forecasting analysis and simulation model can be used as one of inputs to software verification & validation strategy preparation. Keywords - software verification & validation, forecasting, software testing strategy